Corrigendum to “Structure and Expression Kinetics of Piscirickettsia Salmonis Sdha During Infection of Atlantic Salmon Macrophage-Like Cells” [Fish Shellfish Immunol. 168 2025 110929 (Fish and Shellfish Immunology 2026 168 s1050464825008186 (10.1016/J.Fsi.2025.110929)) - Maisey-Munoz, K (Academic Press, 2026)
The authors regret that there was an error in code number for funding projects in the Funding section. It currently reads as: This study was funded by FONDECYT 3210634 (MC), FDP2024-44 (MC), FONDAP 1523A0007 (AR), FONDECYT 1240741 (MI), FONDECYT 1240259 (KM). The revised Funding information is provided below: This study was funded by FONDECYT 3180560 (MC), FDP2024-44 (MC), FONDECYT 3210634 (NV), FONDAP 1523A0007 (AR), FONDECYT 1240741 (MI), FONDECYT 1240259 (KM). The authors would like to apologise for any inconvenience caused. © 2025 Elsevier Ltd